DAYA ANTIPIRETIK EKSTRAK ROSELA (Hibiscus Sabdariffa) - Adhy Nugroho, Christianto (Widya Warta, 2016)
Rosela is one of the medicinal plants, which contain active compounds of flavonoid. The research was conducted to Â determine the antipyretic power of Rosela. This study is a laboratory experiment with mice as test animals. The mice were divided into 3 groups and 4 replications. Group I was the control, without treatment. Groups II and III applied Rosela extract, each of which was 250 mg/kg BW and 500 mg/kg BW. The fever of the mice was induced using DPT vaccine. Rectal temperature was measured every 3 hours for 24 hours. Â The results revealed that Rosela extract possesses antipyretic ability.